VITELLOGENESIS ACTIVITY OF CHANNA MARULIOIDES, BLEEKER, 1851, IMPACT OF FOLICLE STIMULATING HORMONE AS REPRODUCTIVE DOMESTICATION - Rizal. A. Hutagalung; S. Anggoro; Suryanti; M. R. Muskananfola (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study aims to determine the vitelogenesis activity by FSH hormone induction in the early stage of gonadal maturation. The treatament is a differences FSH dose with indicators of vitelogenesis activity were estradiol-17β levels in the blood, Hepatosomatic index (HSI) and Gonadosomatic Index (GSI). The study used a treatment A : Dose FSH at 1.0 ml/kg; B: Dose FSH at 1.25 ml/kg; C : Dose FSH at 1.5 ml/kg; control: nothing induction. The results showed that there was an effect of FSH dose on the estradiol 17β levels, HSI and GSI, there ongoing vitelogenesis activity. The trend of the GSI and HSI has a close correlation to levels of estradiol 17β, with the best dose of the hormone is 1.25 ml/kg resulting levels of esradiol 17β amounting to 63.35 pg / ml and the GSI and HSI are 3.45% and 1.48%. Furthermore, the best treatment successively resulted in increased levels of estradiol 17β, HSI and GSI in treatment C of 41.77 pg/ml, 1.48%, 3.24%; A : 28.01 pg / ml, 1.14 %, 3.42%;. FSH is suitable for reproductive domestication in Channa marulioides.